Effect of hypobaric hypoxia on hematological parameters related to oxygen transport, blood volume and oxygen consumption in adolescent endurance-training athletes - Mancera-Soto, Mónica, E. M.; Chamorro-Acosta L.; Ramos-Caballero, D. M.; Torrella, J. R., Cristancho-Mejía, E. (Journal of Exercise Science & Fitness, 2022)
Background/Objective To analyze the effect of altitude on hematological and cardiorespiratory variables in adolescent athletes participating in aerobic disciplines.